Implementasi Program Muhadharoh sebagai Upaya Meningkatkan Kompetensi Komunikasi Pembelajaran Santri di Pondok Pesantren Modern Al-Mu’awanah Kabupaten Bandung - Wira Khalaf Nurkharis; Mujahid Rasyid (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research is entitled Implementation of the muhadharah program as an effort to improve the learning communication competence of students at the Al-Mu'awanah modern Islamic boarding school, Bandung Regency. This research was conducted to determine muhadharah activities, understand student learning communication and supporting and inhibiting factors for the implementation of the muhadharah program as an effort to improve students' learning communication competence. The aim of this research is to analyze the implementation of the muhadharah program as an effort to improve students' learning communication competence.This research uses a qualitative method with a phenomenological approach. This research uses observation, interview and documentation data collection techniques. This research data analysis technique uses data reduction, data presentation and data verification/drawing conclusions.The results of this research, it was found that (1) the muhadharah activities carried out at the Al-Mu'awanah modern Islamic boarding school were not just ordinary speeches, but used rules and regulations with MC, reading the Al-Qur'an, reciting Islamic vows, taking materials core of students from the audience and entertainment. (2) This muhadharah program is able to act as an effort to improve students' learning communication competence, which can be seen from students' learning communication skills in the classroom. However, at grade level, this ability is still lacking and requires time to learn. (3) The supporting factors that support the implementation of the muhadharah program as an effort to improve the learning communication competence of students: Student language and Management of student organizations. Factors that become obstacles: Students who violate the rules and Management who is not serious during muhadharah. Abstrak. Penelitiaan ini dengan judul Implementasi program muhadharah sebagai upaya meningkatkan kompetensi komunikasi pembelajaran santri di pondok pesantren modern Al-Mu’awanah Kabupaten Bandung. Penelitian ini dilakukan untuk mengetahui kegiatan muhadharah, mengetahui komunikasi pembelajaran santri dan faktor pendukung dan penghambat Implementasi program muhadharah sebagai upaya meningkatkan kompetensi komunikasi pembelajaran santri. Tujuan penelitiaan ini untuk menganalisis Implementasi program muhadharah sebagai upaya meningkatkan kompetensi komunikasi pembelajaran santri.Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis. penelitian ini mengunakan Teknik pengumpulan data observasi, wawancara dan dokumentasi. Teknik analisis data penelitian ini menggunakan reduksi data, penyajian data dan verifikasi data/penarikan kesimpulan. Hasil penelitian ini, ditemukan bahwa (1) kegiatan muhadharah yang dilakukan di pondok pesantren modern Al-Mu’awanah tidak hanya berpidato biasa, namun menggunakan tata tertib, peraturan dengan adanya MC, pembacaan Al-Qur’an, pembacaan ikrar keislaman, pengambilan materi inti oleh santri dari audiens dan adanya hiburan. (2) Program muhadharah ini mampu sebagai upaya untuk meningkatkan kompetensi komunikasi pembelajaran santri dapat dilihat dari kemampuan komunikasi pembelajaran santri di kelas. Namun, pada kelas tingkat bahwa kemampuan ini masih kurang dan butuh proses waktu untuk belajar (3) Adapun faktor pendukung yang menjadi pendukung Implementasi program muhadharah sebagai upaya meningkatkan kompetensi komunikasi pembelajaran santri: Kebahasaan santri dan Pengurus organisasi santri. Faktor yang menjadi penghambat: Santri yang melanggar peraturan dan Pengurus yang tidak serius saat muhadhatah.